STRATEGI PENGEMBANGAN UMKM KOTA BATAM DALAM MENINGKATKAN DAYA SAING DI ERA DIGITAL - Nainggolan, Nora Pitri; Heryenzus, Heryenzus; Situmorang, Robert (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly in terms of employment absorption and contribution to Gross Domestic Product (GDP). However, in the rapidly evolving digital era, MSMEs face new challenges to remain competitive. This study aims to analyze MSME development strategies to increase competitiveness in the digital era. The research method uses a qualitative-descriptive approach with literature studies and field observations of MSMEs in Batam City. The results indicate that digital technology adoption, branding strengthening, human resource capacity enhancement, and government policy support are the main factors driving MSME competitiveness. This study suggests the importance of collaboration between MSMEs, the government, and the private sector in encouraging digitalization and sustainable MSME business innovation.